Praktek Merariq Pada Masyarakat Sasak Di Kecamatan Gerung Kabupaten Lombok Barat - Rosdiana, Rosdiana; Arman, Arman; Multazam, Andi (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2018)
Sasak language Merariq is a verb that is generally meant as a unity of action pre-wedding begins with the escape of girls (the prospective wife) from the supervision of the guardian and simultaneously serve as a procession of early marriage. There are various interpretations in interpret merariq, some interpret it as the process of escape (with the consent of both partners), there are also interpreted as an act of stealing, Sasak language called memaling a girl from the supervision of the person her parents. This research aims to examine and analyze information in depth about the custom merarik. Type a descriptive qualitative research. The results of this research are sasak community interpret merarik as the event of theft of the girl from the parental controls either with the consent or without the consent of a parent or guardian. Most sasak communities do merarik because it has become a tradition of the local community. In this case, Islam does not forbid the practice of merarik origin against corresponding to phases as well as the actual procedure. As for the impact caused is one of them raise the age of marriage of young age. If women get married at a young age a lot once a given impact due to unpreparedness both physical and psychic, in addition, merarik very vulnerable creates a conflict between the two sides if there is one party that is not a registered user agreement. It is hoped this research can contribute to the prevention of marriage due to the young age of merarik. As well as the necessity of granting of socialization to society Sasak about how the nature of the custom merarik is actually so no more self-contradictory the associated practice of merarik.